Queerness and Homophobia in Robin Hobb's Farseer Trilogies. Issue 3 (January 2018) - Melville, Peter
Abstract : This essay explores elements of queerness and homophobia in Robin Hobb's Farseer trilogies. The essay demonstrates how the first trilogy presents its main protagonist, FitzChivalry Farseer, as a character whose closeted experiences as a practitioner of a much-despised magic called the Wit lend themselves as a "substitute alterity" (Balay 934) for the social experience of queer-identifying readers. The essay further considers how Fitz's status as a queer/queer-relatable character becomes even more visible over the second and third trilogies as he struggles to understand his own increasing desire for same-sex intimacy with his best friend the Fool. The series' teasingly belated final image of same-sex union between these two characters, I argue, brings the Farseer trilogies' accumulation of queer allusions and invocations to a tipping point of identifiable clarity, and thus offers a considerable payoff for readers who have followed this aspect of the series with great patience and care for over three decades of publication.